Integration of Islamic Character Education in the Islamic Religious Education Curriculum to Prevent Bullying in High School - Sahri, Sahri; bin Mohd Saufi, Mohd Shahid Azim (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Bullying is one of the social problems that is rampant in the school environment and can have a profound impact on the psychological and social development of students. This study aims to investigate the role of integrating Islamic character values into the Islamic Religious Education (PAI) curriculum in preventing bullying behavior at Al Fattah Islamic High School. This study employs a descriptive qualitative approach, utilizing data collection techniques that include interviews, observations, and documentation studies. The results of the study show that the Islamic Religious Education curriculum in this school incorporates character values such as ukhuwah islamiyah, tasamuh, amar ma’ruf nahi munkar, and empathy; however, its implementation still faces various challenges. Islamic Education teachers have strived to implement contextual learning strategies through discussions, role modeling, and personal approaches, which influence changes in students’ social behavior, especially in fostering empathy and moral awareness. Nevertheless, the process of internalizing values has not progressed evenly and still requires more systemic and collaborative support from school policies. This study recommends strengthening the role of Islamic Education teachers, fostering synergy among teachers, and developing an Islamic character curriculum model as effective strategies for preventing bullying in Islamic-based schools.